2017
DOI: 10.1016/j.livres.2017.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic overexpression of steroid sulfatase alleviates cholestasis

Abstract: Background and Aim Sulfotransferase (SULT)-mediated sulfation and steroid sulfatase (STS)-mediated desulfation represent two critical mechanisms that regulate the chemical and functional homeostasis of endogenous and exogenous molecules. STS catalyzes the hydrolysis of steroid sulfates to form hydroxysteroids. Oxygenated cholesterol derivative oxysterols are known to be endogenous ligands of the liver X receptor (LXR), a nuclear receptor with anti-cholestasis activity, whereas the sulfated oxysterols antagoniz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Recently, we showed that higher levels of circulating steroids are linked to an increased risk of recurrence ( 43 ). Numerous enzymatic pathways are involved in the conversion of both bile acids and steroids, including reduction by aldo-keto reductases ( 49 ), conjugation by uridine diphospho-glucuronosyltransferases ( 50 ), sulfotransferases ( 51 ), and sulfatase ( 52 ). The reduced levels of bile acids may reflect an altered activity of some of these metabolic pathways in R type I cases, consistent with previous findings ( 8 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that higher levels of circulating steroids are linked to an increased risk of recurrence ( 43 ). Numerous enzymatic pathways are involved in the conversion of both bile acids and steroids, including reduction by aldo-keto reductases ( 49 ), conjugation by uridine diphospho-glucuronosyltransferases ( 50 ), sulfotransferases ( 51 ), and sulfatase ( 52 ). The reduced levels of bile acids may reflect an altered activity of some of these metabolic pathways in R type I cases, consistent with previous findings ( 8 , 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we showed that higher levels of circulating steroids are linked to an increased risk of recurrence (43). Numerous enzymatic pathways are involved in the conversion of both bile acids and steroids, including reduction by aldo-keto reductases (49), conjugation by uridine diphospho-glucuronosyltransferases (50), sulfotransferases (51), and sulfatase (52). The reduced levels of bile acids may reflect an altered activity of some of these metabolic pathways in R type I cases, consistent with previous findings (8,42).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to Sult2b1 , Sts catalyses the conversion of sulfated oxysterol to oxysterol ( 30 , 31 ). Therefore, we sought to determine whether the loss of Sts plays an opposing role in the pathological angiogenesis of CNV.…”
Section: Resultsmentioning
confidence: 99%